Evaluating the Effect of Digital Transformation on Improvement of Service Trade in West Africa. Issue 4 (November 2021) - Azu, Nnanna P.; Nwauko, Philip A.
Digital revolution is instrumental to the wave of globalisation and transformation of the global economy. But the pace of digital transformation and service trade is low in the West African region. This article investigates the effect of digital transformation on the development of service trade in the region. This research captured digitisation in two standpoints: internet penetration rate and mobile subscription rate. The Im-Pesaran-Shin unit-root test affirms that the model is appropriate for panel autoregressive distributed lag estimation method. Adopting pool mean group estimator, the results attest for the existence of cointegrations in the model. The estimations reveal that the effect of digitisation on service trade is a long-run phenomenon. While the result is robust with export, it is not consistent with import. The long-run positive impact of digitisation on service export ranges from 0.087% to 0.159%, depending on the proxy for digitisation. The overall short-run effect is not statistically significant in export and not robust in import. It is reportedly consistent in some countries but not robust with some others. The region needs to rally in adopting and adapting to the new face of technology to improve service trade. JEL Codes: C23, F14, O33